Digital organising - Stephan Bohn; Ali Aslan Gümüsay; Georg von Richthofen; Georg Reischauer (Internet Policy Review, 2023)
The digital is pervasive, forming and transforming the ways individual and collective actors organise. We posit digital organising as a key concept that enables researchers and practitioners alike to capture novel forms of organising. Digital organising refers to the collective purposeful alignment and distributed action fostered through digital technologies. We discuss its core processes, datafication and connectification, and how both amplify centralised and decentralised organising. Based on these conceptualisations, we discuss the paradoxical nature of digital organising and offer an outlook for future inquiries.
Keywords: 300; Datafication; Organising; Digital connectivity; Centralisation; Decentralisation